A reposição do gerencialismo neoliberal na gestão dos serviços socioassistenciais no município de Ponta Grossa - Paraná: uma análise a partir do Marco Regulatório das Organizações da Sociedade Civil – Lei 13.019/2014 - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2025)
The aim of this thesis aims is to analyze the implications of neoliberal managerialism on the Management of Social Assistance Services within the Public Social Assistance Policy in the municipality of Ponta Grossa, Paraná, based on the Regulatory Framework for Civil Society Organizations (MROSC). Its specific objectives are: to reflect on the impacts of neoliberal managerialism on the management of social assistance services under the MROSC in Brazil; to understand the implications of using MROSC’s legal instruments for managing Social Assistance Services at the municipal level in the context of neoliberal managerialism; to outline the social assistance network of Ponta Grossa, linked to the municipal public authority through the legal instruments established by the MROSC and its relation to the objectives of the public social assistance policy; and to analyze the main challenges of the management model proposed by the MROSC for delivering social assistance services to the beneficiaries of the social assistance policy, based on insights from public managers and representatives of Civil Society Organizations (CSO) providing these services in Ponta Grossa. This research follows a qualitative approach, grounded in the historical-dialectical materialist method from a Marxist-Gramscian perspective. The research phases include bibliographic, documentary, and field research, the primary data collection instrument is the semi-structured interview, and the data analysis technique follows Laurence Bardin’s content analysis methodology. The thesis is structured into four chapters in the traditional monographic format. The findings confirm the thesis that neoliberal managerialism has been reintroduced into the management of social assistance services within the public social assistance policy through the MROSC in Brazil. This is reflected in the continued logic of minimizing the role of the state by transferring operational responsibilities for these services to civil society. This dynamic is particularly evident in large municipalities such as Ponta Grossa, where the social assistance network is predominantly composed of civil society organizations. a replacement of neoliberal managerialism, translated by the maintenance of the transfer of the State to civil society organizations regarding the execution of public services from the MROSC, receiving insufficient and superficial support from public authorities to strengthen their technical and political capacities in response to new regulations. Thus, this research seeks to contribute to academic discussions by fostering theoretical and practical debates on the subject and providing insights for the management of public social assistance policy, particularly in the municipality of Ponta Grossa.
Keywords: Gerencialismo neoliberal; Gestão Pública; Marco Regulatório das Organizações da Sociedade Civil; Assistência Social; Serviços socioassistenciais; Ciências Sociais Aplicadas